2018
DOI: 10.1074/jbc.ra117.000598
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of translocated in liposarcoma (TLS) inhibits its binding to long noncoding RNA, abrogating TLS-mediated repression of CBP/p300 activity

Abstract: Translocated in liposarcoma (TLS) is an RNA-binding protein and a transcription-regulatory sensor of DNA damage. TLS binds promoter-associated noncoding RNA (pncRNA) and inhibits histone acetyltransferase (HAT) activity of CREB-binding protein (CBP)/E1A-binding protein P300 (p300) on the cyclin D1 () gene. Although post-translational modifications of TLS, such as arginine methylation, are known to regulate TLS's nucleocytoplasmic shuttling and assembly in stress granules, its interactions with RNAs remain poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
3
38
0
Order By: Relevance
“…At the third category, we found hnRNPH1 and TLS which recognize a binding site, 5'(1-1), located in pncRNA-D transcribed from the cyclin D1 gene promoter. Intriguingly, 5'(1-1) has been identified as specific site for TLS [28][29][30]. Our experiments demonstrated that hnRNPH1 also binds the site specific to TLS.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…At the third category, we found hnRNPH1 and TLS which recognize a binding site, 5'(1-1), located in pncRNA-D transcribed from the cyclin D1 gene promoter. Intriguingly, 5'(1-1) has been identified as specific site for TLS [28][29][30]. Our experiments demonstrated that hnRNPH1 also binds the site specific to TLS.…”
Section: Discussionmentioning
confidence: 51%
“…Our binding assays have effectively demonstrated that RBPs have distinctive subgroups classified with criteria of their binding affinity [28,29]. The experiments using random RNA oligos unpredictably indicated that hnRNPUL2 and hnRNPU bind to these RNA oligos which are typically used for negative control of RNA binding assays [28,29,47]. It has been reported that hnRNPUL2 is a part of RNA polymerase II general transcription factor complex [48] and also works on DNA repair processes [49,50], indicating roles in forming nuclear structures.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although arginine methylation has been mostly associated with changes in protein-protein interactions (50,51), there are previous examples of direct modulation of RNA-protein binding in mammalian cells (52)(53)(54). PRMTs have previously been shown to regulate the RNA affinity of target RBPs in other systems (55,56). In T. brucei, the RNA-binding proteins DRBD18 and PRMT1 have been shown to modulate the fate of mRNAs according to methylation state, impacting both protein and mRNA binding (45,50).…”
Section: Discussionmentioning
confidence: 99%